Virtual Laboratories in Tertiary Education: Case Study Analysis by Learning Theories - Jahan Hassan; Anamika Devi; Biplob Ray (MDPI AG, 2022)
This paper examines and evaluates Virtual Laboratories (VLabs) in consideration of technology design, educational pedagogy, and outcome in tertiary education context for ICT courses. There is a growing demand for VLabs in tertiary education to support remote, flexible, and equitable learning. Most of the universities in Australia offer distance education to students who do not attend on-campus classes. On-line labs allowing access via an internet connection can offer learners the required infrastructure to complete their lab tasks without attending physical lab facilities. The onset of COVID-19 pandemic in early 2020 has seen further spike in demand for VLabs as accessing online lab facilities to undertake hands on activities from anywhere and anytime was imperative during lockdown periods. Despite their benefits, it is complex to choose an appropriate VLab design or type that ensures effective and improved learning process. This paper presents two case studies using commercial and custom-made VLabs that are analyzed through the lens of learning theories. The outcome of the analysis informs the readers that the teachers' support (human mediator) and VLabs (teaching tool) are interlinked together in a dialectical way which is an important consideration to achieve successful learning outcome. This study will help educators to make an informed decision in choosing an appropriate VLab design for their teaching content to ensure effective learning outcome.